Calcium-Sensing Receptor Participates in High Glucose-Induced EndMT in Primary Human Aortic Endothelial Cells - Yuan, Cheng; Ni, Lihua; Yang, Xianqin; Zhang, Changjiang; Wu, Xiaoyan (Frontiers in Physiology, 2021)
Objective: Previous studies have shown that high glucose (HG) induces endothelial cell (EC) damage via endothelial-to-mesenchymal transition (EndMT). Although the underlying mechanisms are still unclear, recent studies have demonstrated the role of calcium-sensing receptor (CaSR) in mediating EC damage. Therefore, the aim of our study was to investigate whether CaSR mediates HG-induced EndMT and to determine the underlying mechanism. Methods: Bioinformatics analysis of microarray profiles (GSE30780) and protein-protein interaction (PPI) analyses were performed to select the hub genes. As for in vitro research, the human aortic ECs (HAECs) were exposed to HG to induce EndMT. The expression of CaSR and β-catenin was determined, as well as their effects on EndMT (endothelial marker CD31, mesenchymal marker FSP1 and ɑ-SMA). Results: The bioinformatics analysis indicated CaSR was significantly increased in HG-treated HAECs and was one of the hub genes. The in vitro results showed that HG significantly inhibited the expression of CD31 and increased FSP1 and ɑ-SMA in a concentration- and time-dependent manner. Moreover, CaSR was increased in HAECs after HG treatment. The CaSR antagonist attenuated HG-induced expression of EndMT-related markers. Furthermore, HG treatment increased the nuclear translocation of β-catenin in HAECs. In contrast, blocking the nuclear translocation of β-catenin by DKK1 could attenuate HG-induced EndMT (increased the protein expression of CD31 by 30% and decreased the protein expression of FSP1 by 15% and ɑ-SMA by 25%). CaSR siRNA further inhibited the HG-induced nuclear translocation of β-catenin in HAECs. Conclusion: Our research demonstrated that HG-induced EndMT in HAECs might be mediated by CaSR and the downstream nuclear translocation of β-catenin.